Influence of mycosporine-like amino acids and gadusol on the rheology and Raman spectroscopy of polymer gels - Gaspar Tosato, Maira (2014)
BACKGROUND: The amphiphilic nature of polymers allows them to be widely incorporated as carriers in different pharmaceutical applications since they are able to work as vehicles for hydro- or lipo-soluble actives. OBJECTIVE: The aim of this study was to determine the rheological behavior and vibrational spectral variations of two hydrophilic gels prepared with Poloxamer 407 (PO) or Pluronic F-127 (PL) with the addition of the actives mycosporine-like amino acids and gadusol. METHODS: The structures of these polymers in two different concentrations (20% w/w and 27% w/w) were characterized by rheological studies and Raman spectroscopy. RESULTS: Gels prepared with higher polymer concentration showed larger G′ (storage modulus) values. The C–C stretch and the CH2 rocking predominated in the gels containing PL (20% w/w) and this correlated with a less viscous behavior. The mixture of the actives induced higher contributions of Raman peaks related to trans conformation of the C–C bonds located in hydrophilic polymer blocks, whereas the same peaks decreased in the sample containing only gadusol. CONCLUSIONS: Larger tensile strength and elastic component were observed upon increasing polymer concentration, thus evidencing polymer–polymer and/or polymer–polymer–actives interactions. The presence of the actives affected the mechanical properties of the polymer gels. Gadusol particularly seems to alter the conformation of the polymer chains by favoring gauche orientations, in parallel with rising viscoelastic parameters. More stretched arrangements of the polymer are probably induced in the presence of larger concentration of actives, due to specific interactions with their hydrophilic groups.